Pengembangan Rubrik Penilaian Formatif untuk Memberikan Umpan Balik pada Esai Peserta Didik Materi Energi Terbarukan Kelas X SMA - Yolanda Eyducia Silaban; Ridwan Abdullah Sani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The assessment of students' essay responses in physics learning is often constrained by subjective scoring, inconsistent evaluation, and limited feedback that supports learning improvement. This study aimed to develop a formative assessment rubric to provide feedback on students’ essays in the topic of renewable energy for Grade X senior high school students. The research employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Data were collected through interviews, questionnaires, expert validation sheets, teacher practicality questionnaires, and students’ pretest and post-test results. The content validity of the rubric was evaluated using Aiken’s V, while reliability was measured using Cronbach’s Alpha. Practicality was determined through teacher response questionnaires, and effectiveness was assessed using the N-gain test. The results indicated that the developed rubric achieved a very high level of validity based on expert judgment. Reliability testing showed coefficients of 0.889 in the small-scale trial and 0.9902 in the large-scale trial, indicating very high reliability. The practicality score reached 88.54%, categorized as practical. Furthermore, the effectiveness test revealed moderate to high N-gain scores, indicating that the rubric and the feedback provided were effective in improving students’ understanding of renewable energy concepts. Therefore, the developed formative assessment rubric is valid, reliable, practical, and effective for assessing students’ essays and providing meaningful feedback in physics learning.